An economic assessment of stand-level treatments for southern pine beetle prevention - Naumann, Nathaniel (SLU/Southern Swedish Forest Research Centre, 2012)
The Southern Pine Beetle (SPB) (Dendroctonus frontalis) is a native pest of pine trees in the Southeast US. It is the most significant pest of forests in the region (Fettig et al., 2007). The potential effect of silvicultural treatments on reducing damages from southern pine beetle depends on treatments and the assumed probability of damages in a region. This research evaluated the stand level benefits and costs of prevention treatments used to reduce damages from Southern Pine Beetles. For the 13 southern states, a broad set of treatments were applied to a set of representative stands to characterize the SPB Prevention Program impacts. The representative stands were used in a growth and yield model and were projected into the future under various conditions and treatments. The products from the growth and yield model were then used to estimate soil expectation value (SEV), which was adjusted to account for the risk associated with the probability of tree mortality from SPB (Martell, 1980). The probability of tree mortality from SPB was generated from United States Forest Service (USFS) Forest Inventory and Analysis (FIA) data across the Southeast (Pye et al., 2008). Results indicated that planted stands would benefit from commercial thinning treatments when compared to control treatments. Pre-commercial thinning treatments resulted in lower SEVs than the control or commercial thinning treatments for planted stands. Results for natural stands suggested that control (no treatment) led to higher SEVs than commercial thinning treatments. The results suggest that components of the prevention program may not be financially justified in terms of stand level SEVs. However, further research is necessary to determine if the ecological effects of the treatments warrant financial support for the program.